EFEKTIVITAS PENERIMAAN NEGARA BUKAN PAJAK (PNBP) PADA KANTOR KESYAHBANDARAN DAN OTORITAS PELABUHAN KELAS IV TEGAL - Ulul Absor; Amsirun Amsirun; Mia Secilia Aprianti (Jurnal Strategik, 2022)
Abstraksi  This research is entitled "Effectiveness of Non-Tax State Revenue (PNBP) at the Class IV Tegal Harbor Authority and Harbor Authority Offices".The formulation of the problem posed is:1. What is the effectiveness and efficiency of Non-Tax State Revenue at the Class IV Tegal Port Authority and Port Authority Offices?2. How is the realization of Non-Tax State Revenue at the Tegal Class IV Port Authority and Harbormaster Office?3. What is the projection of Non-Tax State Revenue at the Tegal Class IVHarbormaster and Port Authority Office?The results of this study obtained are that the level of effectiveness of NonTax State Revenue (PNBP) of Class IV Tegal Harbor and Authority Offices from 2017 to 2021 has an average rate of 181.16 percent, so it can be said to have a very good level of effectiveness or very effective. Meanwhile, the efficiency level of Non-TaxState Revenue (PNBP) for Class IV Tegal Port Authority and Harbormaster Offices from 2017 to 2021 has an average rate of 104.51 percent.This can be interpreted that the efficiency level of Non-Tax State Revenue (PNBP) of Class IV Tegal Port Authority and Harbormaster Offices is not good.